Practices and challenges of school improvement program in Waghimra administrative zone, Amhara region, Ethiopia - Tadesse Merawi; Abraham Desta; Desalegn Tiruye; Getachew G/Egziabhe; Turuwark Warkineh; Yismaw Mekuriya (College of education, Bahir Dar University, 2023)
The main purpose of this study was to investigate practices and challenges of school improvement program [SIP] in Waghimra Administrative Zone. Mixed methods approach with concurrent design was utilized, and data were collected from randomly selected 1,033 primary and secondary school teachers, 10 school principals, 11 woreda and zone education experts, 13 student representatives and nine Parent Teacher Student Association (PTSA) and Kebele Education and Training Board (KETB) members using questionnaire, interview, focus group discussion, and document reviews. The collected data were analyzed quantitatively using one sample t-test and one-way ANOVA and qualitatively using descriptions. The findings revealed that the planning and execution of the SIP and its domains (teaching-learning, leadership, learning environment and community participation) were low in the administraive zone with variations among woredas. Due to the lack of qualified and experienced teachers and school principals, the teaching and assessment practices were not effective. School principals' capability of planning and executing SIP was also insufficient. Most primary and secondary schools of the zone (99%) were below the expected standards. Community participation in the school affairs falls below expectation. Accordingly, continuous capacity building training on SIP, methods of teaching, assessment, curriculum development, and instructional leadership need to be provided for teachers, school principals and woreda and zone education experts. Besides, to construct standard schools and fulfill educational facilities, involving various stakeholders (governmental and non-governmental organizations and volunteer individuals and the community at large) is a timely concern.